Fifteen emerging challenges and opportunities for vegetation science: A horizon scan by early career researchers. (25th February 2022) - Yannelli, Florencia A.; Bazzichetto, Manuele; Conradi, Timo; Pattison, Zarah; Andrade, Bianca O.; Anibaba, Quadri Agbolade; Bonari, Gianmaria; Chelli, Stefano; Ćuk, Mirjana; Damasceno, Gabriella; Fantinato, Edy; Geange, Sonya R.; et al.
Abstract: With the aim to identify future challenges and opportunities in vegetation science, we brought together a group of 22 early career vegetation scientists from diverse backgrounds to perform a horizon scan. In this contribution, we present a selection of 15 topics that were ranked by participants as the most emergent and impactful for vegetation science in the face of global change. We highlight methodological tools that we expect will play a critical role in resolving emerging issues by providing ways to unveil new aspects of plant community dynamics and structure. These tools include next generation sequencing, plant spectral imaging, process‐based species distribution models, resurveying studies and permanent plots. Further, we stress the need to integrate long‐term monitoring, the study of novel ecosystems, below‐ground traits, pollination interactions and global networks of near‐surface microclimate data at fine spatio‐temporal resolutions to fully understand and predict the impacts of climate change on vegetation dynamics. We also emphasize the need to integrate traditional forms of knowledge and a diversity of stakeholders into research, teaching, management and policy‐making to advance the field of vegetation science. The conclusions reached by this horizon scan naturally reflect the background, expertise and interests of a representative pool of early career vegetation scientists, which should serve as basis for future developments in the field. Abstract : We performed a horizon scan to identify future challenges and opportunities for vegetation science. Fifteen topics were selected as the most emergent and impactful for the field. These include methodological and conceptual tools to improve predictions, unveil new aspects of plant community dynamics and structure, as well as critical areas of knowledge, advancing research and policy‐making.